Advanced energy design guide for small to medium office buildings : achieving zero energy (ASHRAE, 2019)
"Provides recommendations for achieving a net zero energy small or medium office building; allows contractors, consulting engineers, architects, and designers to easily achieve advanced levels of energy savings without resorting to detailed calculations or analyses"-- Provided by publisher
Earlier edition produced by American Society of Heating, Refrigerating and Air-Conditioning Engineers. 2011.
Keywords: Office buildings -- Energy conservation.; Office buildings -- Design and construction -- Standards.; Buildings -- Mechanical equipment.; elektronické knihy; electronic books